2009
DOI: 10.1007/s10096-009-0825-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and antimicrobial susceptibility profiling of Gram-positive cocci in blood cultures with the Vitek 2 system

Abstract: Rapid identification and antimicrobial susceptibility profiling of the bacteria in blood cultures can result in clinical and financial benefits. Addition of saponin to the fluid from blood culture bottles promotes the recovery of the bacteria and thus may shorten the turnaround time of the microbiological analyses. In this study we compared the identification and susceptibility profiles of saponin-treated and untreated (standard method) blood cultures monomicrobial for Gram-positive cocci using Vitek 2. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Nonetheless, occurrence of very major errors seem to be recurrent when testing the susceptibility to some antimicrobials such as ampicillin for Gram-negative bacilli (8,19). On the other hand, the absence or very low rate of errors for the susceptibility testing of Gram-positive cocci toward vancomycin is common (8,14,19). Using the VITEK 2 system some bacteria in our study were not identified or were misidentified and various levels of disagreement in the susceptibility testing were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, occurrence of very major errors seem to be recurrent when testing the susceptibility to some antimicrobials such as ampicillin for Gram-negative bacilli (8,19). On the other hand, the absence or very low rate of errors for the susceptibility testing of Gram-positive cocci toward vancomycin is common (8,14,19). Using the VITEK 2 system some bacteria in our study were not identified or were misidentified and various levels of disagreement in the susceptibility testing were found.…”
Section: Discussionmentioning
confidence: 99%
“…The VITEK system used in the present study was developed by bio Mérieux as an automated system for identification and antimicrobial susceptibility testing and was later improved into the VITEK 2 system. The improved version automates all mandatory steps for identification and antimicrobial susceptibility testing after a standardized inoculum has been loaded into the system (13 Various studies have evaluated the performance of the VITEK 2 system for identification of Gram-negative and -positive bacteria associated with bacteraemia (13,14), but the results vary across studies. This variability does not allow clear and definite conclusions about the performance of the system for both identification and susceptibility testing.…”
Section: Introductionmentioning
confidence: 99%
“…To shorten the turnaround time required for diagnosis of BSI, the fluid from a positive blood culture bottle may be directly inoculated into an automated system for ID and AST of bacteria, further referred to as direct methods (Figure 1). Several studies have compared the results of the current blood culture method with those by direct methods [10][11][12][13][14][15][16][17][18]. The direct method has been shown to yield reliable results very stable and with a strong signal to noise ratio.…”
Section: Variations To the Standard: Direct Inoculation Methodsmentioning
confidence: 99%
“…Treatment with detergents, such as saponin, before inoculation into the appropriate ID and AST cards improves the recovery of Gram-positive cocci as well as P. aeruginosa from positive blood culture, probably by releasing intracellular bacteria from human blood cells [18]. Although some isolates may be missed or misidentified by the direct method, a good categorical agreement between the direct and standard methods is usually observed for AST results, with relatively low overall error rates for the direct method [13,14,17,18]. The main sources of errors by direct methods are mixed cultures and a too small inoculum size.…”
Section: Assessment Of β-Lactamase Mediated Resistance By Maldi-tofmentioning
confidence: 99%
See 1 more Smart Citation